KESADARAN BERBUDI LUHUR DALAM BERMEDIA SOSIAL UNTUK MENGHINDARI TINDAKAN UJARAN KEBENCIAN MENURUT AGAMA HINDU - Arsana, I Nyoman Alit; Purnawati, Ni Wayan; Ningsih, Cryshna Selistya (Widya Katambung, 2024)
Social Media has become an important part of people's lives amidst the development of information technology. The development of information technology, especially social media, has had many positive and negative impacts. The negative impact is hate speech. Technological advances give perpetrators influence in carrying out hate speech because of the availability of tools and facilities that are easy to obtain. These facilities include ease of obtaining a smartphone, multiple facilities or features, profile cloning. This convenience should be accompanied by legal awareness, especially the Information and Electronic Transactions (ITE) Law and having noble character. Hindu religious teachings which teach the creation of noble character and essentially everything is oriented towards fostering ethics and noble character.